2003
DOI: 10.1590/s0004-282x2003000300024
|View full text |Cite
|
Sign up to set email alerts
|

Cauda equina hemangioblastoma: case report

Abstract: -Hemangioblastomas of the spinal cord are rare lesions, and those located at the cauda equina are even rarer. Most commonly these tumors are present in patients with von Hippel-Lindau (VHL) syndrome. We describe here the case of a 48 years old woman with a pure radicular hemangioblastoma, not associated with VHL, presenting with radicular pain, diagnosed with magnetic ressonance imaging (MRI) and submitted to total resection with a very good outcome. To our knownledge, this is the second report to describe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Browne et al 8 and Yasargil et al 12 reported an incidence of 21.3% and 25.3%, respectively, for this type of presentation of this tumor. In 2003, Costa Jr et al 15 described an exceptional case of cauda equina hemangioblastoma diagnosed by MRI, in a 48-years-old woman without VHL, who presented with paresthesia and discreet weakness in the left leg.…”
Section: Fig 3 [A] Histological Section Showing the Proliferation Ofmentioning
confidence: 99%
“…Browne et al 8 and Yasargil et al 12 reported an incidence of 21.3% and 25.3%, respectively, for this type of presentation of this tumor. In 2003, Costa Jr et al 15 described an exceptional case of cauda equina hemangioblastoma diagnosed by MRI, in a 48-years-old woman without VHL, who presented with paresthesia and discreet weakness in the left leg.…”
Section: Fig 3 [A] Histological Section Showing the Proliferation Ofmentioning
confidence: 99%
“…Primary tumors of the filum terminale and conus medullaris, or both, comprise only 6% of spinal cord tumors 2 . Only 6.2% to 7.5% of all intraspinal tumors are vascular 3,4 .The cavernous angioma rarely occurs in the cauda equina. The literature reports eleven cases [5][6][7][8][9][10][11][12][13][14] .…”
mentioning
confidence: 99%
“…6 Extramedullary-intradural hemangioblastomas of the nerve roots are rare and represent one fifth of all spinal hemangiobalstomas. [7][8][9][10][11][12][13][14][15][16][17] Most of these are associated with von Hippel-Lindau disease. Michaud et al 18 reported a 6-month-old infant with a spinal cord hemangioblastoma located in the conus medullaris in association with an overlying congenital dermal sinus and cutaneous capillary hemangioma.…”
Section: Discussionmentioning
confidence: 99%